2013
DOI: 10.7314/apjcp.2013.14.4.2515
|View full text |Cite
|
Sign up to set email alerts
|

Total Laparoscopic Hysterectomy Versus Total Abdominal Hysterectomy for Endometrial Cancer: A Meta-analysis

Abstract: The standard surgery for early-stage endometrial cancer is total abdominal hysterectomy (TAH), while total laparoscopic hysterectomy (TLH) is less invasive and assumed to be associated with lower morbidity. This metaanalysis was performed to investigate the effects of TLH versus TAH in women with early-stage endometrial cancer. We searched the PubMed, EMBASE, CBM and Cochrane Review databases for randomized trials assessing the effects of TLH versus TAH in women with early-stage endometrial cancer. The relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Endometrial cancer is the most common gynecologic cancer treated with laparoscopic surgery. It is feasible and has less operative morbidity, less blood loss, shorter hospitalizations, and better short-term quality of life than the laparotomy approach (Kornblith et al, 2009;Galaal et al, 2012;Wang et al, 2013). Similar results were reported for laparoscopic radical hysterectomy in cervical cancer (Magrina et al, 2008).…”
Section: Introductionsupporting
confidence: 74%
“…Endometrial cancer is the most common gynecologic cancer treated with laparoscopic surgery. It is feasible and has less operative morbidity, less blood loss, shorter hospitalizations, and better short-term quality of life than the laparotomy approach (Kornblith et al, 2009;Galaal et al, 2012;Wang et al, 2013). Similar results were reported for laparoscopic radical hysterectomy in cervical cancer (Magrina et al, 2008).…”
Section: Introductionsupporting
confidence: 74%
“…Surgery is the mainstay of staging and treatment but chemotherapy and radiotherapy are also used in selected patients. Total laparoscopic hysterectomy or total abdominal hysterectomy may be preferred options (Wang et al, 2013). Observation, whole pelvic radiotherapy, brachytherapy and chemotherapy are all treatment options recommended for stage IB disease in NCCN guidelines but which treatment for which particular patient is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain more consistent evidence regarding the effects of laparoscopy in EEC, Wang et al recently conducted a meta-analysis of randomized trials quantitatively evaluating clinical outcomes including complications and mortality rate [10]. Wang et al confirmed the results of 2 previous meta-analyses [8,20], showing evidence of a benefit for laparoscopy over laparotomy in the surgical staging of women with EEC (Table 2).…”
Section: Surgical Approach With Eec (Stage I Figo2009)mentioning
confidence: 88%